PENERAPAN MODEL KONSERVASI LEVINE PADA PEMENUHAN KEBUTUHAN CAIRAN DAN ELEKTROLIT ANAK YANG DIRAWAT - Agustin, Diah Ayu (Indonesian Journal of Nursing Health Science, 2018)
Fluids and electrolytes are part of the energy conservation children need to adapt to maintain the full function of the body. The purpose of this study was to provide an overview of the application of the Levine conservation model in treated children with fluid and electrolyte problems. The method of this study is a case study by applying Levine conservation model to five children treated with fluid and electrolyte problems. The results of the evaluation of treatment of the five cases of fluid and electrolyte problems showed that the problem was solved, only one case had not been resolved because the client experienced a deterioration when about to go home. Conclusion: The Levine conservation model is well suited to the fulfillment of fluid and electrolyte needs of treated children. Â Keywords: levine conservation model, fluids and electrolytes, treated child